50.2k views
2 votes
(12 - 5)2 + (83 - 9x6)

(12 - 5)2 + (83 - 9x6)-example-1
User Ksav
by
4.9k points

2 Answers

2 votes

Answer:


78

Explanation:


(12-5)^2+(83-9*6)

Follow the PEMDAS order of operations

Calculate within parentheses
(12-5)


12-5


12-5=7


=7


=7^2+(83-9*6)

Calculate within parentheses
(83-9*6)

Multiply and divide (left to right)


9*6


9*6=54


=54

Add and subtract (left to right)


83-54


83-54=29


=29


=7^2+29

Calculate exponents
7^2


7^2


7^2=49


=49


=49+29

Add and subtract (left to right)
49+29


49+29


49+29=78


=78

User Shai Levy
by
4.9k points
5 votes

Answer:

78

Explanation:

Solve by PEMDAS.

Parentheses first.

12-5 is 7 and 9x6 is 54, 83-54 is 29.

(7)^2+(29)

Exponent next,

49+29

add them up and you get 78.

Hope this helps! Hit the crown if you want.

#Team Rainbows!

User Petr Syrov
by
4.9k points